Novel fluorescence probe for estimation of cysteine/histidine in human blood plasma and recognition of endogenous cysteine in live Hct116 cells - Reddy, Upendar G.; Agarwalla, Hridesh; Taye, Nandaraj; Ghorai, Suvankar; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2014)
A new Cu(II)-complex is used as a ``Turn-On'' luminescence probe for specific detection of endogenous Cys in live Hct116 cells and Cys present in human blood plasma without any interference from other amino acids, especially GSH and Hcy. Difference in the mechanistic pathway for Cys and His recognition is discussed.